160k views
4 votes
7p − p = 18 2) −5n − 4n = −9

User JegsVala
by
4.7k points

2 Answers

4 votes
Answer: p = 3 , n = 1
Step by step explanation
7p-p = 18
6p = 18
p = 3
Finding n
-5n-4n = (-9)
-9n = (-9)
n = -9/-9
n = 1
Hope it helped comment below!,
User AlexMomotov
by
5.0k points
2 votes

Answer:


\boxed{ \bold{ \sf{ \boxed{ p = 3}}}}


\boxed{ \bold{ \sf{ \boxed{n = 1}}}}

Explanation:

1.
\sf{7p - p = 18}

Collect like terms


\sf{6p = 18}

Divide both sides of the equation by 6


\sf{ (6p)/(6) = (18)/(6) }

Calculate


\sf{p = 3}

2.
\sf{ - 5n - 4n = - 9}

Collect like terms


\sf{ - 9n = - 9}

Divide both sides of the equation by -9


\sf{ ( - 9n)/( - 9) = ( - 9)/( - 9) }

Calculate


\sf{n = 1}

Hope I helped!

Best regards!!

User Anindit Karmakar
by
4.8k points